The effect of HMG-CoA reductase inhibitors on naturally occurring CD4+CD25+ T cells - Mausner-Fainberg, Karin; Luboshits, Galia; Mor, Adi; Maysel-Auslender, Sophia; Rubinstein, Ardon; Keren, Gad; George, Jacob (Atherosclerosis, 2008)
Hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors (statins) are in widespread use due to their LDL reducing properties and concomitant improvement of clinical outcome in patients with and without preexisting atherosclerosis. Considerable evidence suggests that immune mediated mechanisms play a dominant role in the beneficial effects of statins. Naturally occurring CD4+CD25+ regulatory T cells (Tregs) have a key role in the prevention of various inflammatory and autoimmune disorders by suppressing immune responses. We tested the hypothesis that statins influence the circulating number and the functional properties of Tregs. We studied the effects of in vivo and in vitro statin treatment of human and murine mononuclear cells on the number of Tregs and the expression level of their master transcription regulator, Foxp3. Atorvastatin, but not mevastatin nor pravastatin, treatment of human peripheral blood mononuclear cells (PBMCs) increased the number of CD4+CD25high cells, and CD4+CD25+Foxp3+ cells. These Tregs, induced by atorvastatin, expressed high levels of Foxp3, which correlated with an increased regulatory potential. Furthermore, co-culture studies revealed that atorvastatin induced CD4+CD25+Foxp3+ Tregs were derived from peripheral CD4+CD25−Foxp3− cells. Simvastatin and pravastatin treatment in hyperlipidemic subjects increased the number of Tregs. In C57BL/6 mice however, no effect of statins on Tregs was evident. In conclusion, statins appear to significantly influence the peripheral pool of Tregs in humans. This finding may shed light on the mechanisms governing the plaque stabilizing properties of statins.